2018
DOI: 10.1007/s12015-018-9840-y
|View full text |Cite
|
Sign up to set email alerts
|

Elevated Numbers of Circulating Very Small Embryonic-Like Stem Cells (VSELs) and Intermediate CD14++CD16+ Monocytes in IgA Nephropathy

Abstract: IgA nephropathy (IgAN) is recognized as most frequent form of primary glomerulonephritis worldwide. IgAN is associated with renal degradation occurring due to irreversible pathological changes leading to glomerulosclerosis and interstitial fibrosis. It remains poorly understood whether and to what extent these changes are followed by the activation of regenerative mechanisms. Therefore, in this study we aimed to evaluate regenerative potential of IgAN patients by quantitating the frequencies of several stem ce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
18
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 22 publications
(21 citation statements)
references
References 48 publications
(47 reference statements)
2
18
0
Order By: Relevance
“…Similar to our results, lower amounts of CD14++ monocytes have been described in patients with multiple sclerosis (MS) [34] and juvenile idiopathic arthritis (JIA) with enthesitis [35]. Besides, a higher percentage of CD16+ intermediate and non-classical monocytes with a pro-inflammatory phenotype has been described in patients with MS [34], neuromyelitis optica [36], RA [18], SLE [37], ANCA-vasculitis [38], sarcoidosis [39], IgA nephropathy [40], JIA with enthesitis [35], type 1 diabetes mellitus [41], thromboembolism [42], atherosclerosis and stroke [43] which is according to our results. Also, we found that the absolute number of classical monocytes inversely correlated with the disease activity (MYOACT and MITAX), which is according with previous data in patients with RA, where there is a higher percentage of intermediate monocytes during disease activity and a higher proportion of classical monocytes during remission [44].…”
Section: Discussionsupporting
confidence: 88%
“…Similar to our results, lower amounts of CD14++ monocytes have been described in patients with multiple sclerosis (MS) [34] and juvenile idiopathic arthritis (JIA) with enthesitis [35]. Besides, a higher percentage of CD16+ intermediate and non-classical monocytes with a pro-inflammatory phenotype has been described in patients with MS [34], neuromyelitis optica [36], RA [18], SLE [37], ANCA-vasculitis [38], sarcoidosis [39], IgA nephropathy [40], JIA with enthesitis [35], type 1 diabetes mellitus [41], thromboembolism [42], atherosclerosis and stroke [43] which is according to our results. Also, we found that the absolute number of classical monocytes inversely correlated with the disease activity (MYOACT and MITAX), which is according with previous data in patients with RA, where there is a higher percentage of intermediate monocytes during disease activity and a higher proportion of classical monocytes during remission [44].…”
Section: Discussionsupporting
confidence: 88%
“…In general, VSELS recovery was reported more efficient using erythrocyte lysis when compared to the "5th layer method" [211]. More recently, clinical investigations on peripheral blood VSELS content followed no other method as in bone marrow or umbicilical cord blood however, having chosen a stain-then-lyse then-wash protocol and using 600 uL of sample blood [212] as opposed to the first lyse-then-stain method. Also, Ratajczak et al [209] and his group proposed a three step method briefly consisting of red blood cell lysis, followed by positive selection of CD133+cells using immuno -magnetic cell separation technology, and thirdly, FACS-based isolation of small CD133+Lin−CD45− cells.…”
Section: Very Small Embryonic Stem Cell General Backgroundmentioning
confidence: 99%
“…VSELS quantification as such VSELS elevation was shown in various pathologies, including nephropathies, vascular pathologies, MI, pulmonary hypertension, chronic obstructive pulmonary disease, stroke, active inflammatory bowel disease or solid tissue cancer and leukemias. Glomerulonephritis, in particular IgA nephritis has been investigated by Eljaszewicz et al [212] showing elevation specifically in VSELS when compared to other stem cells when tested in parallel, that included HSC, EPC as well as different monocyte subsets with varying maturation and angiopoietic potential. Also, MI may be associated with VSELS elevation [213][214][215].…”
Section: Vsel Stem Cell Clinical Usefulnessmentioning
confidence: 99%
“…Monocytes represent a heterogenic population of immune cells, which, according to differences in CD14 and CD16 expression, can be divided into three functionally different subsets, namely classical (CD14++CD16-), intermediate (CD14++CD16+), and nonclassical (CD14+CD16++) monocytes. In physiological conditions, all three subsets, respectively, represent successive stages of monocyte maturation [5,6]. Classical CD14++CD16-monocytes constitute the predominant subset of blood monocytes (80-90%).…”
Section: Introductionmentioning
confidence: 99%